Beach almond, treasure of the islands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
There is a tree with a great many uses that grows in the South Pacific called Terminalia catappa; it is more commonly known as the 'beach almond' or 'natapoa'. It reaches a height of between 25 and 40 metres, its deep roots help to protect beach...